Use of Photobiomodulation Combined with Fibrin Sealant and Bone Substitute Improving the Bone Repair of Critical Defects - Pomini, Karina Torres; Buchaim, Daniela Vieira; Bighetti, Ana Carolina Cestari; Andreo, Jesus Carlos; Rosso, Marcelie Priscila de Oliveira; Escudero, José Stalin Bayas; Della Coletta, Bruna Botteon; Alcalde, Murilo Priori; Duarte, Marco Antonio Hungaro; Pitol, Dimitrius Leonardo; Issa, João Paulo Mardegan; Ervolino, Edilson [UNESP]; et al. (MDPI, 2022)
In this preclinical protocol, an adjunct method is used in an attempt to overcome the limitations of conventional therapeutic approaches applied to bone repair of large bone defects filled with scaffolds. Thus, we evaluate the effects of photobiomodulation therapy (PBMT) on the bone repair process on defects filled with demineralized bovine bone (B) and fibrin sealant (T). The groups were BC (blood clot), BT (B + T), BCP (BC + PBMT), and BTP (B + T + PBMT). Microtomographically, BC and BCP presented a hypodense cavity with hyperdense regions adjacent to the border of the wound, with a slight increase at 42 days. BT and BTP presented discrete hyperdensing areas at the border and around the B particles. Quantitatively, BCP and BTP (16.96 ± 4.38; 17.37 ± 4.38) showed higher mean bone density volume in relation to BC and BT (14.42 ± 3.66; 13.44 ± 3.88). Histologically, BC and BCP presented deposition of immature bone at the periphery and at 42 days new bone tissue became lamellar with organized total collagen fibers. BT and BTP showed inflammatory infiltrate along the particles, but at 42 days, it was resolved, mainly in BTP. In the birefringence analysis, BT and BTP, the percentage of red birefringence increased (9.14% to 20.98% and 7.21% to 27.57%, respectively), but green birefringence was similar in relation to 14 days (3.3% to 3.5% and 3.5% to 4.2%, respectively). The number of osteocytes in the neoformed bone matrix proportionally reduced in all evaluated groups. Immunostaining of bone morphogenetic protein (BMP—2/4), osteocalcin (OCN), and vascular endothelial growth factor (VEGF) were higher in BCP and BTP when compared to the BC and BT groups (p < 0.05). An increased number of TRAP positive cells (tartrate resistant acid phosphatase) was observed in BT and BTP. We conclude that PBMT positively influenced the repair of bone defects filled with B and T.
Keywords: biomaterial; bone repair; bone substitute; fibrin sealant; low-level laser therapy; photobiomodulation therapy; polymers; scaffolds